HEALTHCARE UNDER EUROPEAN UNION INTERNAL MARKET LAW - Janeckaitė, Rūta (Teisė, 2016)
In the context of ongoing and future discussions regarding possible reorganization of the Lithuanian healthcare system in accordance with the constitutional requirements, this article strives to contribute to the discussions by showing the potential of the application of the freedoms of the internal market to healthcare. In particular, it examines the extent to which the freedom of services and the freedom of establishment are applicable to healthcare, and analyses the basis for the Union competence in the healthcare area and its limits. It also aims to establish, where the current European Union (EU) law strikes a balance between the internal market and the power of the Member States to organise their social security (healthcare) systems.The principles of free movement within internal market were designed, in essence, with economical considerations in mind, whereas healthcare is often perceived from the national point of view as a service of public interest exclusively falling under the national competence. However, through the broad interpretation by the Court of Justice of the EU of the notions of the internal market, such as “services”, “companies or firms” and „restrictions“, the principles of free movement were brought to apply to full extent to healthcare. Almost any activity within the healthcare sector is therefore an economical activity from the point of view of the internal market freedoms and falls under the scope and scrutiny of EU law.Nevertheless, the article shows that the development of EU law in the area is not monolitic. The practical consequences in the field of the application to healthcare of the freedom of services are far more reaching than in the field of the freedom of establishment, where a certain reservation on the part of the Court of Justice of the EU might be currently observed.